Nutrimental composition and physicochemical parameters of thermosonicated soursop nectar - Anaya-Esparza, Luis M.; Méndez-Robles, María D.; Pérez-Larios, Alejandro; Yahia, Elhadi M.; Montalvo-González, Efigenia (TIP Revista Especializada en Ciencias Químico-Biológicas, 2017)
Effect of thermosonication (TS) at two different experimental conditions [TS1 = 24 kHz, 1.3 W/mL of acoustic energy density (AED), 51 °C for 8 min and TS2 = 24 kHz, 1.4 W/mL AED, 54 °C for 10 min] on the nutrimental composition and physicochemical parameters of soursop nectar stored at 4 ºC were evaluated. Fresh (untreated) and traditionally pasteurized (65 °C, 30 min) soursop nectars were used as controls. TS did not cause changes in the most nutrients and physicochemical parameters evaluated. However, it was measured a highest dietary fiber content (33 %), turbidity (30%) and viscosity (5%), when TS2 was applied. The soluble dietary fiber is one of the functional compounds with demonstrated potential effects on the health; therefore TS could increase the functional quality of soursop nectar. Also, the changes in some physicochemical characteristics improved its physical appearance. TS can be considered an excellent alternative to process soursop beverages.